Applicability of pressure retarded osmosis power generation technology in Istanbul - Pasaoglu, Mehmet Emin; Koyuncu, Ismail; Sengur-Tasdemir, Reyhan; Guclu, Serkan; Turken, Turker; Budeyri, Bilge; Baykan, Orhan; Daskiran, Filiz; Tezcan, Elif (International University of Sarajevo, 2018)
In this study, the applicability of pressure retarded osmosis power generation was investigated in order to meet the electricity demand in Turkey. Pressure retarded osmosis (PRO) is a method that converting salinity gradients to power using a semi-permeable membrane against an applied pressure and PRO is one of the promising candidates to reduce fossil fuel dependency. In PRO, water is transported from a low concentrated feed solution to a high-concentrated draw solution. According to the literature findings, in order to produce 1MW of electricity 1m3/s fresh water flow is needed. Turkey is surrounded on three sides by water and has a big potential to develop this technology. Riva River is investigated in the scope this study. Currently Turkey’s total installed power capacity reached 85.200 MW at the end of 2017.Calculations of PRO power generation reveals that it is possible to generate 25,45 MW, If using 5% of total river flow.